If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -4n = 11 + 2n Solving 13 + -4n = 11 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 13 + -4n + -2n = 11 + 2n + -2n Combine like terms: -4n + -2n = -6n 13 + -6n = 11 + 2n + -2n Combine like terms: 2n + -2n = 0 13 + -6n = 11 + 0 13 + -6n = 11 Add '-13' to each side of the equation. 13 + -13 + -6n = 11 + -13 Combine like terms: 13 + -13 = 0 0 + -6n = 11 + -13 -6n = 11 + -13 Combine like terms: 11 + -13 = -2 -6n = -2 Divide each side by '-6'. n = 0.3333333333 Simplifying n = 0.3333333333
| (3*5-5)(5-1)=x | | 4p-5=18 | | -7b-5(b-4)= | | x^2-7x-7=0 | | x^2+10x+39=-3x+3 | | 3x^3-17x^2=6x | | 14n-3(nt-4)= | | x^2-3x+5=9 | | 2b^2-16b=0 | | 3x-5+x=31 | | (x^2+3x+9)(2x^3+3x-4)(4x^2+2x^2-8x)= | | 8(6x+3)+3x=x | | 3x+18=x+2 | | 25*2.3=0 | | 25*2.3= | | P(x)=x^3-7x^2+17x-15 | | 4+(7*25)20-38=x | | 25*2.3=57.5 | | 4x^2+11x+5=-4x+2 | | 3x+18=x+3 | | 13a-6(a+5)=x | | 3x^3+4-2x^4= | | 82-3*8=x | | 4x^2-27x+37=-3x+2 | | 82-3*(5-3)3=x | | (7b-3)+(b-4)=646 | | y^2+10Y+25=121 | | a^2+14a-18=0 | | -12(x-4)=-138 | | z^2+12z-25=0 | | (6x^3+7x+12)-(3x^2+8x+8)= | | -3+2x=19 |